Central African Republic : Use of Fund Resources-Request for Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Use of Fund Resources-Request for Post-Conflict Emergency Assistance on the Central African Republic (CAR) focuses on the political situation and post-conflict economic recovery. The post-conflict economic recovery remains subdued. Fiscal reforms will focus on boosting revenue and containing expenditure. Revenue measures will center on tightening controls in tax administration and fighting fraud at customs. Reforms in the governance area are directed at fighting corruption mainly through enhanced transparency and strengthening the judiciary with a view to improving the management of public resources.